Mills's Statistical Methods - Crum, W. L.; Mills, Frederick Cecil (Quarterly Journal of Economics, 1925)
Journal Article Mills's Statistical Methods Get access W. L. Crum W. L. Crum Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 39, Issue 3, May 1925, Pages 469–472, https://doi.org/10.2307/1882437 Published: 01 May 1925